Body mass composition of ballet dancers and elite female aesthetic sport athletes from Cuba. - Hamlet Betancout León; Oscar Salinas Flores; Julieta Aréchiga Viramontes (Universidade Federal de Santa Catarina, 2011)
The level of scenic beauty of ballet dancer's figure is signified for the reason of possessing morpho-functional characteristics valid only within the artistic cannon. The female ballet dancers and the sportswomen who practice esthetic sports do have in common the need of being slim and executing efficiently the complex movements of their technical activities. The objective of this paper is to compare the body composition of ballet female dancers with that of the artistic gymnastics (GAR), the rhythmic gymnastics (GRI) and the synchronized swimming (NAS) elite sportswomen. Thirty two female ballet dancers of the National Cuban Ballet School and sixty three elite sportswomen who practice aesthetic sports in Cuba have been studied for the purpose. An anthropometric protocol of sixteen measures has been applied to calculate the kinanthropometric indexes of the corporal mass composition's component. The general percentage of the fat mass (PMG) in the ballet dancers was found statistically different to the GAR and GRI groups, but this one was similar in comparison with NAS group. Mayor muscle mass general percentage (PMM) was obtained in the GAR and GRI groups, in comparison with the dancers. The ballet group showed the minor differential PMM-PMG, and muscular percentage of the transverse areas of the segments of extremities than the elite athlete groups. The data classified the ballet group as the one of less potential efficiency of technical and transitive movement than the other ones.